(untitled) (Architecture Image Studies, 2026)
The rapid digitalization of work and learning environments has led to an overwhelming influx of information, often resulting in information overload that may impair productivity. This study aims to systematically examine the relationship between information overload and work productivity across various digital populations, including students, employees, and professionals. Using a Systematic Literature Review (SLR) approach guided by the PRISMA method and the PICOC framework, 60 peer-reviewed articles from Scopus and Google Scholar were analyzed. The findings indicate that information overload negatively affects work efficiency, quality of outcomes, engagement, and psychological well-being. However, under certain conditions, such as high digital literacy and effective information management strategies, information overload can foster innovation and productivity. The impact of information overload is moderated by contextual factors including role type, technological environment, and coping strategies. This review provides critical insights for organizations and educational institutions to design adaptive policies and tools that mitigate the adverse effects of information overload in digital work ecosystems.